Charles Loloma the Pacesetter - DeWald, Louise (New Mexico Magazine, 1977)
This article is about the Hopi artist Charles Loloma and his jewelry creations.
3p/double sided New Mexico Magazine article
Master list item #: 20
File location is in the New Mexico file Cabinet
Keywords: Loloma, Charles; Indian Jewelry; Hopi Indian Artist; Indian Art; Artist History; New Mexico